2018
DOI: 10.1002/ps.5085
|View full text |Cite
|
Sign up to set email alerts
|

Increased virulence in the locust‐specific fungal pathogen Metarhizium acridum expressing dsRNAs targeting the host F1F0‐ATPase subunit genes

Abstract: Our results demonstrate that dsRNA expression in M. acridum can cause host RNA silencing during infection and greatly enhances the fungal virulence through interference with critical host genes, highlighting a new strategy for augmentation of fungal virulence against insect pests. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 50 publications
(95 reference statements)
0
25
0
Order By: Relevance
“…Fungal‐induced gene silencing (FIGS) has also been employed to enhance RNAi in insect pests. FIGS has been explored in two main ways: by engineering common fungi, like Saccharomyces cerevisiae or Pichia pastoris , 48,63 to express target dsRNAs, or by engineering entomopathogenic fungi to express dsRNAs that will enhance their virulence 64‐66 . S. cerevisiae and P. pastoris are commonly used in laboratory settings for a variety of experiments on genetics and heterologous expression of proteins, so modification of these fungi is relatively easily achieved.…”
Section: Strategies For Enhancing Rnai Efficiencymentioning
confidence: 99%
“…Fungal‐induced gene silencing (FIGS) has also been employed to enhance RNAi in insect pests. FIGS has been explored in two main ways: by engineering common fungi, like Saccharomyces cerevisiae or Pichia pastoris , 48,63 to express target dsRNAs, or by engineering entomopathogenic fungi to express dsRNAs that will enhance their virulence 64‐66 . S. cerevisiae and P. pastoris are commonly used in laboratory settings for a variety of experiments on genetics and heterologous expression of proteins, so modification of these fungi is relatively easily achieved.…”
Section: Strategies For Enhancing Rnai Efficiencymentioning
confidence: 99%
“…Application of RNAi‐mediated pest control relies on a stable dsRNA delivery system. Some delivery systems have been suggested to be effective in pest control, including genetic modification of host plants, use of bacterial, viral, and or fungal agents, as well as potentially direct feeding and/or spray applications of dsRNA . Similar to what has been shown in other insects, LmIAP1 has the potential to be developed for locust control through these dsRNA delivery systems.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of chemical pesticides in locust control has been recognized as being unsustainable for safeguarding various ecosystems. Expression of an insect toxin or host targeting dsRNA in wild‐type insect pathogenic fungi have been confirmed as promising strategies to improve the speed of kill of Metarhizium to locust. These findings indicate that continued research in locust control is needed and our data show that use of synergistic strategies that combine different approaches can yield a more effective product that may ultimately reduce costs, improve efficiency and persistence, and increase agricultural sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…Methods including nanoparticles, transfection reagents and dsRNA encapsulation using bacteria or plastids are potential techniques to increase dsRNA stability. Transferring or delivery of the dsRNA of a target gene into a plant, virus and/or fungal pathogen that would in turn ‘deliver’ the dsRNA to the target insect has been demonstrated in several cases, and a similar approach can now be used regarding nxf1 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been shown that the virulence of an insect pathogen can be improved via expression of a dsRNA targeting the insect F1F0‐ATPase subunit gene. These studies indicate that expression in the locust‐specific fungal pathogen Metarhizium acridum offers a means of dsRNA delivery to locusts . Engineering of these fungal pathogens has shown significant potential in targeted pest control, including for vectors of human disease‐causing agents such as mosquitoes .…”
Section: Introductionmentioning
confidence: 99%